O conhecimento matemático do professor: formação e prática docente na escola básica - Plínio Cavalcanti Moreira; Maria Manuela Martins Soares David (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article, analyse the process of formation for mathematics teachers at undergraduate level, confronting the mathematical knowledge transmitted in this process with some of the issues the teacher is faced with at school. The study focuses on the natural number system and refers to the undergraduate degree in mathematics at the Federal University of Minas Gerais (UFMG), in Brazil. The sources used include textbooks on numbers (at school and university levels), syllabus specifications for the referred course and the research literature on mathematics education. We describe part of the mathematical knowledge (about natural numbers) involved in professional teaching practice at elementary school. We also point out some concrete forms taken on by the formation/teaching practice dichotomy, thus contributing to a better understanding of this important and much debated issue.